Amplified electrochemical sensor employing Ag NPs functionalized graphene paper electrode for high sensitive analysis of Sudan I. (1st March 2022) - Meng, Fanxing; Qin, Yanan; Zhang, Wenrui; Chen, Fei; Zheng, Li; Xing, Jun; Aihaiti, Aihemaitijiang; Zhang, Minwei
Highlights: Ag nanoparticles were employed as signal amplification for detection of Sudan I. Graphene oxide as flexible substrate was used to construct disposable electrode. As-constructed paper-based electrode exhibited high sensitivity and selective for Sudan I detection in chili powder. Abstract: In this study, a high-performance flexible reduced graphene oxide (rGO) paper electrode composed of silver nanoparticles (Ag NPs) for the detection of Sudan I was fabricated. Ag NPs were doped with rGO nanoheets by self-assemble and assembled into a paper electrode with layer-by-layer structure via vacuum filtration. Thanks to the highly efficient electrocatalysis of Ag NPs towards reduction of azo bond, the as-prepared hybrid paper can be used alone as a flexible sensor for the detection of Sudan I in chili powder, with the high sensitivity (22.93 μA μmol/L) and the low detection limit (41.3 nmol/L). The sensor also expressed good selectivity, repeatability, reproducibility, stability and recovery between 96.1% and 101.8% (RSD < 6%). With the advantages of low-cost and scalable production capacity, such Ag NPs/rGO functional papers can be used as flexible disposable sensors for electrochemical detection of Sudan I.